Budaya Transaksional dalam Kelas Menengah, Diametral Pilihan antara Idealisme dan Pragmatisme (dalam Perspektif Sociological Imagination C.Wright Milss) - Prananta, Arie Wahyu; Abidin, Zainal (representamen, 2020)
Abstract This article is to understand, analyze and interpret the movement diametrically space between idealism and pragmatism transaksionalisme cultural anti middle class groups conducted by using sociological perspectives Imagination C. Wright Mills. This article tries to find that the room is diametrically between idealism and pragmatism that appeared in diametraletis middle class anti-culture transaksionalisme get that high integrity to break away from the role of private and public roles, venue selection in anti culture transaksionalisme so they choose a place that can accommodate their anti-mainstream and dare to get out of your comfort zone, to change the system, although the risk will become a person who alienated, unpopular and always in solitude space. Diametric between idealism and pragmatism and for groups in the area of anti-culture transaksionalisme lighter because dilemma ethical in the role of his own, while a group in the area of power and politics is heavier because some can only see and experience the shock remarkable to stress but do not have the power to report it, some others even splashed in the cultural world transaksionalisme. Keywords: Idealism, Pragmatism, diametraletis, sociological imagination